Impact of disease‐modifying therapies on humoral and cellular immune‐responses following SARS‐CoV‐2 vaccination in MS patients. Issue 7 (4th March 2022) - Trümpelmann, Susan; Schulte‐Mecklenbeck, Andreas; Steinberg, Olga V.; Wirth, Timo; Fobker, Manfred; Lohmann, Lisa; Lünemann, Jan D.; Wiendl, Heinz; Gross, Catharina C.; Klotz, Luisa
Abstract: The impact of distinct disease‐modifying therapies (DMTs) on severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) vaccination efficacy in patients with multiple sclerosis (MS) is still enigmatic. In this prospective comparative study, we investigated humoral and cellular immune‐responses in patients with MS receiving interferon beta, natalizumab, and ocrelizumab pre‐vaccination and 6 weeks post second SARS‐CoV‐2 vaccination. Healthy individuals and interferon beta‐treated patients generated robust humoral and cellular immune‐responses. Although humoral immune responses were diminished in ocrelizumab‐treated patients, cellular immune‐responses were reduced in natalizumab‐treated patients. Thus, both humoral and cellular immune responses should be closely monitored in patients on DMTs. Whereas patients with a poor cellular immune‐response may benefit from additional vaccination cycles, patients with a diminished humoral immune‐response may benefit from a treatment with SARS‐CoV‐2 antibodies in case of an infection.